A Dwarfing Gene sd1-d (Dee-geo-woo-gen dwarf) on Lodging Resistance and Related Traits in Rice - Bhattarai, Mukunda; Kamimukai, Misa; Rana, Birendra Bahadur; Oue, Hiroki; Matsumura, Shinji; Murai, Masayuki (Journal of Nepal Agricultural Research Council, 2021)
A dwarfing allele at the sd1 locus on chromosome 1 in rice, sd1-d, has been playing important role for developing lodging-resistant and high-yielding indica varieties IR8 and IR36. The dominant allele SD1 for long culm at the locus is differentiated into SD1-in and SD1-ja that are harbored in indica and japonica subspecies, respectively. The sd1-d of IR36 was substituted with SD1-in or SD1-ja by 17 backcrosses with IR36, and two isogenic tall lines were developed by using an indica variety IR5867 and a japonica one ‘Koshihikari’ as donors, which were denoted by “5867-36” and “Koshi-36’’, respectively. The present study was conducted to examine the effect of dwarfing gene sd1-d on lodging resistance and related traits, compared with SD1-in and SD1-ja. Two isogenic lines and IR36 were cultivated in the field of the Faculty of Agriculture and Marine Science, Kochi University, Japan during 2017. Regarding index of lodging (g·cm/g × 100), genotypes were in the order: 5867-36 (97.4) > Koshi-36 (74.1) > IR36 (46.0) on the 21st-day after 80%-heading, and they were in the same order on 10th-day after 80%-heading. The 4th-panicle length (cm) was in the order: 5867-36 (118.7) > Koshi-36 (97.6) > IR36 (78.6). Similarly, the 4th-top weight (g) was in the order: 5867-36 (12.2) > Koshi-36 (10.2) > IR36 (9.6). The highest breaking strength (g) was recorded in IR36 (1649) followed by 5867-36 (1493) whereas the lowest breaking strength (g) was recorded in Koshi-36 (1360). Consequently, it is inferred that sd1-d enhances lodging resistance due to the decreases in the length and weight above the 4th-internode as well as the increase of breaking strength. The effect of SD1-in on lodging resistance is lower than that of SD1-ja.